The Initial Educational Content of Theatre as a Subject Implemented in 11th or 12 th Grades by Pre-service Theatre Teachers: Relevant and Broad - Kazragytė, Vida (Pedagogika, 2019)
This article presents the results of an investigation into the initial educational content of theatre subject in 11th or 12th grades in Lithuania. It is shown, that the initial educational content of theatre subject is devoted to obviate the negative pupils’ attitudes to themselves and their inabilities to interact. Also, to achieve an expressing pupil’s individual point of view, creating respectful relationships, behaving as a co-creator.